The teacher will be very surprised to see your correct solution 😉

Detail solution

Given the linear equation:

Looking for similar summands in the left part:

Move the summands with the other variables

from left part to right part, we given:

$$9 x = 6 - 18 y$$

Divide both parts of the equation by 9

We get the answer: x = 2/3 - 2*y

9*x+18*y = 6

Looking for similar summands in the left part:

9*x + 18*y = 6

Move the summands with the other variables

from left part to right part, we given:

$$9 x = 6 - 18 y$$

Divide both parts of the equation by 9

x = 6 - 18*y / (9)

We get the answer: x = 2/3 - 2*y

Rapid solution
[src]

x1 = 2/3 - 2*re(y) - 2*I*im(y)

$$x_{1} = - 2 \operatorname{re}{\left(y\right)} - 2 i \operatorname{im}{\left(y\right)} + \frac{2}{3}$$

x1 = -2*re(y) - 2*i*im(y) + 2/3